Civic legacies of wartime governance - Patricia Justino; Wolfgang Stojetz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
In conflict zones around the world, both state and non-state actors deliver governance at local levels. This paper explores the long-term impact of individual exposure to 'wartime governance' on social and political behaviour. We operationalize wartime governance as the local policy choices and practices of a ruling actor. Building on detailed ethnographic and historical insights, we use survey data and a natural experiment to show that involvement in wartime governance by armed groups makes Angolan war veterans more likely to participate in local collective action twelve years after the end of the war. This effect is underpinned by a social learning mechanism and a shift in political preferences, but has no bearing on political mobilization at the national level or social relations within the family. Our study documents an important institutional legacy of civil wars and exposes challenges and opportunities for bottom-up approaches to post-conflict state-building and local development.
Keywords: P37; D74; H56; 330; conflict; civil war; wartime governance; post-conflict state-building; local development